2013
DOI: 10.1002/cb.1405
|View full text |Cite
|
Sign up to set email alerts
|

The halo model of origin images: Conceptualisation and initial empirical test

Abstract: National origin has gained importance as a marketing tool for practitioners to sell their goods and services. However, because origin-image research has been troubled by several fundamental limitations, academia has become sceptical of the current status and strategic implications of the concept. The aim of this paper was threefold, namely, to provide a state-of-the-art review of origin-image research in marketing, develop and empirically test a new origin-image model and, present the implications of the study. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(130 citation statements)
references
References 96 publications
12
115
0
3
Order By: Relevance
“…One important reason for the challenge is associated with their country of origin, which is one of the critical dimensions of moral legitimacy (Zarkada-Fraser and Fraser, 2002). In the marketing literature, the country of origin (COO) effect has been an important research issue for a long time (e.g., Bilkey and Nes, 1982;Diamantopoulos et al, 2011;Josiassen et al, 2013). A key research interest of these studies is whether and how the country of origin of products and services influence consumers' attitude or purchase intention.…”
Section: Institutional Theory and Construct Developmentmentioning
confidence: 99%
“…One important reason for the challenge is associated with their country of origin, which is one of the critical dimensions of moral legitimacy (Zarkada-Fraser and Fraser, 2002). In the marketing literature, the country of origin (COO) effect has been an important research issue for a long time (e.g., Bilkey and Nes, 1982;Diamantopoulos et al, 2011;Josiassen et al, 2013). A key research interest of these studies is whether and how the country of origin of products and services influence consumers' attitude or purchase intention.…”
Section: Institutional Theory and Construct Developmentmentioning
confidence: 99%
“…One key to understanding how an association to a place can affect consumer judgment is the influence of categories (Josiassen et al , ). This influence can be exemplified by examining the case of Colombian coffee.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the effect of categories and their role in the context of origin effect (Niffenegger et al , ; Roth and Romeo, ; Diamantopoulos et al , ; Josiassen et al , ). It has been suggested that the COE is stronger for categories that are relatively closely associated with a particular place (O'Shaughnessy and O'Shaughnessy, ) as exemplified in the case of the country Colombia and the product category coffee.…”
Section: Introductionmentioning
confidence: 99%
“…Closely correlated to the concept of mere exposure, a particular effect, called the halo effect, comes on observers (Josiassen et al, 2013). The halo effect affects attitudinal changes of people towards a product or a brand name to which they are exposed (Lee & Lockshin, 2010).…”
Section: Sponsor's Exposure and Halo Effectmentioning
confidence: 99%